PHOTOGRAPHY AS NECESSITY IN EVERYDAY AESTHETIC LIFE - MAVROPOL, Andra (Studia Universitatis Babeș-Bolyai Philosophia, 2015)
Photography as Necessity in Everyday Aesthetic Life. The aesthetic in everyday life is necessarily linked to an interior experience of the world we live in. In this frame of reference, the outlook of this article is that of highlighting the importance of photography as a required practice of recording and sharing experiences. Although the value of each experience is intrinsic, one may notice that the necessity of keeping the significant states of consciousness in an aesthetic wrap, along with sharing them with the rest of the world places us in an artistic mindset, but that does not necessarily make us artists.